Paroxysmal atrial fibrillation ablation with a novel flexible tip radiofrequency catheter incorporating contact force sensing: acute results of the TactiFlex AF IDE trial. (3rd October 2022) - Nair, D; Martinek, M R; Colley, J; Sundaram, S; Hariharan, R; Morales, G; Sommer, P; Healy, S; Siddiqui, U; Williams, C; Sarver, A; Lo, M
Abstract: Background: Catheter ablation is an established therapy for paroxysmal atrial fibrillation (PAF). The TactiFlex™ Ablation Catheter, Sensor-Enabled™ (TactiFlex SE) is a next-generation radiofrequency ablation catheter incorporating highly accurate fiber optics-based contact force sensing technology with a flexible, laser-cut tip. Purpose: To demonstrate that ablation with TactiFlex SE is safe and effective for the treatment of drug refractory, symptomatic PAF. Methods: The TactiFlex AF IDE is a prospective, non-randomized, multi-center clinical study which enrolled 355 subjects worldwide. Enrollment in the main study began on June 26, 2020 and completed on June 18, 2021. Subjects underwent de novo Pulmonary Vein Isolation (PVI) and, if indicated, a Cavotricuspid Isthmus ablation (CTI line) for CTI-dependent atrial flutter. Results: Subjects were divided into two as treated subgroups: High Standard Power (HSP, n=189), defined as subjects with 100% of left atrial lesions ablated at ≥40 W, and Low Standard Power (LSP, n=119), defined as subjects with at least one left atrial lesion ablated at <40W. First pass success, defined as isolation of all pulmonary veins (PVs) confirmed after a minimum 20 min waiting period was achieved in 93.5% (175/186) and 84.5% (98/116) of HSP and LSP subjects, respectively (p=0.0104). Significant decreases in the HSP versus LSP procedures were also seen in total procedure time (112.0 min [89.0, 139.5] and 149.0 [115.0, 182.0], respectively [p<0.001]), total RF time for PV ablation (14.0 min [11.0, 19.0] and 29.0 [19.0, 41.0], respectively [p<0.0001]), total fluoroscopy time (4.0 min [0.0, 11.0] and 8.0 [3.0, 17.0], respectively [p<0.0001]) and irrigation fluid volume (378.0 mL [310.0, 466.0] and 636.0 [476.0, 829.0], respectively [p<0.0001]) (values given as Median [Q1, Q3]), see Figure 1. Both HSP and LSP subjects had a low rate of repeat procedures (1.6% [3/182] and 4.3% [5/115], respectively [p=0.2684]) and primary safety endpoint events (4.8% [9/189] and 4.2% [5/119], respectively [p=0.8182]) through 90 days post-index procedure. Conclusion: The acute data on the TactiFlex SE catheter demonstrates safe and effective treatment of PAF using either a HSP or LSP ablation strategy. Ablation procedures performed using a HSP strategy were shorter and required less irrigation fluid and fluoroscopy. It is anticipated these results will be reflected in the 12-month safety and effectiveness primary endpoints. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott